Analisis Pemahaman Konsep Suhu Kalor & Gelombang Bunyi pada Siswa SD Kelas VI MIS Alquba Medan - Suyit Ratno; Indri Khairunnisa Erwinsyah; Trisna Natalia BR Parapat; Syahkira Sifah Nasution; Saskia Nurul Ain; Annisa Hapsari; Selvi Simanjuntak; Dimas Pramadana Ginting (Universitas 45 Surabaya, 2025)
This research aims to analyse the understanding of class VI students at MIS Alquba Medan about the concepts of temperature, heat, and sound waves. The method used is a quantitative approach with descriptive design, where data is collected through questionnaires and direct observations. The results of the study showed that there was an increase in student understanding after the explanation of the material was done with interactive learning media. In addition, several common misconceptions among students were also identified. The applied learning method is proven to be effective in increasing students' understanding of physics concepts. Hopefully, this finding can provide valuable insight for educators in an effort to improve the quality of science learning at the elementary school level.